1998
DOI: 10.1046/j.1523-1755.1998.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting solute clearance in peritoneal dialysis

Abstract: Small solutes clearances cannot be increased by furosemide. Increasing the instilled volume of dialysis fluid and the number of exchanges both affect solute clearance. Studies are necessary on long-term effects of manipulation of the peritoneal membrane with nitroprusside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 37 publications
2
24
0
1
Order By: Relevance
“…Large dialysate volumes are often required to increase solute clearance for patients undergoing peritoneal dialysis (1,2). Theoretically, the increased solute clearance obtained with the use of large volumes (2-4) could be attributable either to an increased blood/dialysate solute concentration gradient or to an increase in the effective peritoneal surface area.…”
Section: ϫ2mentioning
confidence: 99%
See 1 more Smart Citation
“…Large dialysate volumes are often required to increase solute clearance for patients undergoing peritoneal dialysis (1,2). Theoretically, the increased solute clearance obtained with the use of large volumes (2-4) could be attributable either to an increased blood/dialysate solute concentration gradient or to an increase in the effective peritoneal surface area.…”
Section: ϫ2mentioning
confidence: 99%
“…The surface area was estimated by using stereologic methods. After instillation of the 2-L solution, the volume of the peritoneal solution at the time of CT scanning was 2.32 Ϯ 0.05 L. The PSA-CD was 0.57 Ϯ 0.03 m 2 , ranging from 0.41 to 0.76 m 2 . The use of the 3-L solution increased the peritoneal volume by 46 Ϯ 2%.…”
mentioning
confidence: 99%
“…More recently, a randomized controlled trial has been published in abstract form, 38 which showed that long‐term frusemide therapy (250 mg per day) in 60 incident PD patients produced a statistically and clinically significant increase in urine volume over a 6‐month period (+185 ± 117 vs. control −151 ± 100 mL/24 h, P = 0.036) but had no effect on residual renal function 38 . Thus, diuretics may be helpful in controlling fluid overload in PD patients 18,39 . However, there is no high‐level clinical evidence to support their use in maintaining residual renal function.…”
Section: Strategies For Maintaining and Optimizing Residual Renal Clementioning
confidence: 99%
“…urea). On the other hand, peritoneal diffusive capacity is accentuated by the conditions listed in Table 2 and is more important for the clearance of larger weight molecules 18 …”
Section: Determinants Of Peritoneal Clearancementioning
confidence: 99%
“…Initially, this type of medication was used with the hope of preserving or even increasing RRF [7]. Recent studies show that even though UV increases after drug administration, the use of these drugs is not actually related to alterations in clearance of solutes [9].…”
Section: Introductionmentioning
confidence: 99%